Return the soul to education - Abd Razak, Dzulkifli (2010)
THERE was another low-key but significant event alongside the 5th Islamic Conference of Ministers of Higher Education and Scientific Research (ICMHESR) organised by Innovation and Islamic Educational, Scientific and Cultural Organisation last week.